MOUNTAINS OF "GREEN": ANALYZING THE VISUAL RHETORIC OF MOUNTAINTOP REMOVAL. - BRAGG, RACHEL LANIER (Journal of Appalachian Studies)
Mountaintop removal has long been a contentious practice in the Appalachian Mountain region. It is fraught with complexities and controversies and is often positioned between debates about economic development and environmental sustainability. This conflict has been complicated by the movement toward green energy. Drawing on the principles and theories of document design, this paper analyzes how visual rhetoric is utilized in two documents, "Mountaintop Mining: Viewpoint" and "Appalachian Voices: Annual Report," to communicate the relationship between mountaintop removal and environmental sustainability.